Qualidade da carne de caprinos SRD e seus cruzamentos com Boer e Anglo Nubiano terminados em confinamento - Cabral, Humberto Barbosa (2011)
There is a large group of Undefined Breed (UDB) goats in the Brazilian Northeast that are characterised by low meat production. However, crossing these animals with goats that are pure bred for meat production can improve their meat production capabilities. The goal of this study was to evaluate the quantitative and qualitative characteristics of meat from UDB goats and their hybrids with the Anglo Nubian and Boer breeds. Thirty non-castrated goats, including 10 UDB, 10 ½ Anglo Nubian x ½ UDB and 10 ½ Boer and ½ UDB, with an average age of 150 days and an average initial live weight of 19.05 kg were used. Genotype had no effect on the marbling of the meat, as determined by real-time ultrasound. Cholesterol concentrations in the meat from ½ Anglo Nubian x ½ UDB goats were lower than those in the other genotypes. We also detected a higher percentage of saturated fat and, consequently, a lower percentage of unsaturated fat in the UDB goats. The measurements of shear force, water-holding capacity, weight lost due to cooking and chemical composition of the goat meat were not affected by genotype. The goats that were part Anglo Nubian or Boer had a higher intensity of red colour in the meat, both in the objective evaluation and the subjective evaluation. The meat from the Anglo Nubian x UDB and Boer x UDB genotypes had higher lipid quality than the meat from the UDB goats. Crossing the Anglo Nubian and Boer breeds with UDB goats reduces the percentage of saturated fats and increases unsaturated fat in meat.